Cytokine Profiles of Severe Influenza Virus-Related Complications in Children - Fiore-Gartland, Andrew; Panoskaltsis-Mortari, Angela; Agan, Anna A.; Mistry, Anushay J.; Thomas, Paul G.; Matthay, Michael A.; , PALISI PICFlu Investigators; Hertz, Tomer; Randolph, Adrienne G.; Sanders, Ronald C.; Hefley, Glenda; Tellez, David; et al. (Frontiers in Immunology, 2017)
Effective immunomodulatory therapies for children with life-threatening “cytokine storm” triggered by acute influenza infection are lacking. Understanding the immune profiles of children progressing to severe lung injury and/or septic shock could provide insight into pathogenesis. The objective of the study was to compare the endotracheal and serum cytokine profiles of children with influenza-related critical illness, and to identify their associations with severe influenza-associated complications. Children with influenza-related critical illness were enrolled across 32 hospitals in development (N=171) and validation (N=73) cohorts (December 2008 through May 2016). Concentrations of 42 cytokines were measured in serum and endotracheal samples and clustered into modules of covarying cytokines. Relative concentrations of cytokines and cytokine modules were tested for associations with acute lung injury, shock requiring vasopressors, and death/ECMO. Modules of covarying cytokines were more significantly associated with disease severity than individual cytokines. In the development cohort, increased levels of a serum module containing IL6, IL8, IL10, IP10, GCSF, MCP1 and MIP1α (shock OR = 3.37, FWER-p < 10-4), and decreased levels of a module containing EGF, FGF2, SCD40L and PAI-1 (shock OR = 0.43, FWER-p = 0.002), were both associated with acute lung injury, shock and death-ECMO independent of age and bacterial coinfection. Both of these associations were confirmed in the validation cohort. Endotracheal and serum cytokine associations differed markedly and were differentially associated with clinical outcomes. We identified strong positive and negative associations of cytokine modules with the most severe influenza-related complications in children, providing new insights into the pathogenesis of influenza-related critical illness in children. Effective therapies may need to target mediators of both inflammation and repair.